Xylem Sap Proteomics Reveals Distinct Differences Between R Gene- and Endophyte-Mediated Resistance Against Fusarium Wilt Disease in Tomato - de Lamo, Francisco J.; Constantin, Maria E.; Fresno, David H.; Boeren, Sjef; Rep, Martijn; Takken, Frank L. W. (Frontiers in Microbiology, 2018)
Resistance (R) genes and endophytic organisms can both protect plants against pathogens. Although the outcome of both processes is the same, little is known about the commonalities and differences between both immune responses. Here we set out to phenotypically characterise both responses in the tomato-Fusarium pathosystem, and to identify markers to distinguish these responses at the molecular level. As endophyte Fusarium oxysporum (Fo) strain Fo47 was employed, which confers protection against various pathogens, including the vascular wilt fungus F. oxysporum f.sp. lycopersici (Fol). As R-gene conferring Fol resistance the I-2 gene of tomato (Solanum lycopersicum) was used. Fol colonizes the xylem vessels of susceptible and I-2 resistant tomato plants, but only causes disease in the former. Fol was found to colonize the vasculature of endophyte-colonized plants, and could be isolated from stems of non-diseased plants co-inoculated with Fo47 and Fol. Because the xylem vessels form the main interface between plant and pathogen, the xylem sap proteomes during R gene- and Endophyte-Mediated Resistance (RMR and EMR) were compared following label-free quantitative nLC-MS/MS. Surprisingly, both proteomes were remarkably similar to the mock, revealing only one or two differentially accumulated proteins in the respective resistant interactions. Whereas in I-2 plants the accumulation of the pathogenesis-related protein PR-5x was strongly induced by Fol, the endophyte triggered induction of both NP24, another PR-5 isoform, and of a ß-glucanase in the presence of Fol. Notably, over 54% of the identified xylem sap proteins have a predicted intracellular localization, which implies that these might be present in exosomes. In conclusion, whereas both resistance mechanisms permit the pathogen to colonize the vasculature, this does not result in disease and this resistance coincides with specific induction of the two distinct PR-5 isoforms and a ß-glucanase.